Tradisi Mebanten Tebasan Pada Hari Penampahan Galungan Di Desa Beringkit Belayu Kecamatan Marga Kabupaten Tabanan - Ni Nyoman Rai Triyantini (Vidya Darsan: Jurnal Mahasiswa Filsafat Hindu, 2021)
The life activities of Hindus in Bali will never be separated from the routine of the yajna. From the presence of the seed in the womb, birth to maturity, the existence of the yajna is firmly attached. Hindus apply their religious teachings in various yajna activities to manifest gratitude to Sang Hyang Widhi Wasa so it is not surprising that the existence of the yajna has become an identity for Hindus in Bali. So in this case the yajna activity is carried out because it is a part of the obligations of Hindus. Mebanten Tebasan is one of the Manusa Yajna ceremonies. In the village of Beringkit Belayu, there is a tradition on the day of Penampahan Galungan. The tradition is Mebanten Tebasan, the uniqueness of this tradition is that it is only intended for boys who have already scratched their teeth. The technique of determining the informants in this study is by using purposive sampling technique. Data collection methods are participant observation, semi-structured interviews, documentation and literature. The collected data were analyzed using qualitative descriptive analysis method. With steps, namely reduction, data presentation, and drawing conclusions. The results of this study are (1) The procession begins with slaughtering the pork in the morning, then processing the pork into lawar, tum, meat, stock, fried meat, and others, making banten tebasan, at 18.00 wita natab banten tebasan and nglebar banten tebasan. (2) The values of Hindu religious education in the tradition of mebanten tebasan are: Religious Values, Ethical Values, Sincerity Values, and Aesthetic Values. Key words: Mebanten, Tebasan, Penampahan Galungan